2013
DOI: 10.17239/jowr-2013.04.03.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Word Processor as an Accommodation for Students with Learning Disabilities

Abstract: examined wrote two gender, et ''interactio accommo longer ess regardless smaller pe time for w Keywords

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It is commonly believed that such accommodations are helpful (Lovett & Leja, 2013); however, we know little about the effects of these accommodations on students’ test performance and learning, the validity of test scores generated under nonstandard conditions, and possible iatrogenic effects of accommodations on students who receive them and their classmates who do not (Lovett & Lewandowski, 2015). For example, only a handful of published studies have examined the efficacy of access to technology during exams, such as word processors (Berger & Lewandowski, 2013; Lovett, Lewandowski, Berger, & Gathje, 2010) and calculators (Bouck, 2009; Bouck & Yadav, 2008; Engelhard, Fincher, & Domaleski, 2010). These studies have generally found that technology benefits all students, regardless of their disability classification.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly believed that such accommodations are helpful (Lovett & Leja, 2013); however, we know little about the effects of these accommodations on students’ test performance and learning, the validity of test scores generated under nonstandard conditions, and possible iatrogenic effects of accommodations on students who receive them and their classmates who do not (Lovett & Lewandowski, 2015). For example, only a handful of published studies have examined the efficacy of access to technology during exams, such as word processors (Berger & Lewandowski, 2013; Lovett, Lewandowski, Berger, & Gathje, 2010) and calculators (Bouck, 2009; Bouck & Yadav, 2008; Engelhard, Fincher, & Domaleski, 2010). These studies have generally found that technology benefits all students, regardless of their disability classification.…”
Section: Discussionmentioning
confidence: 99%
“…Hollenbeck, Tindal, Stieber, and Harris (1999) found that for middle school students with SLDs, essays were rated higher on traits such as content, organization, ideas, and conventions when written by hand. For college students with and without SLDs, Berger and Lewandowski (2013) found that students in both groups wrote longer essays when word processing, and reported preferring composing by keyboard. Additionally, the effects of word-processing upon writing can differ depending upon whether the participants are writing over longer periods of time (with multiple drafts, as in 22 of the 27 studies reviewed in Morphy and Graham (2012) or are writing “on-demand” compositions within a shorter time period, as on a test (Russell & Plati, 2000).…”
Section: Specific Learning Disabilities In Writingmentioning
confidence: 97%
“…Overall results showed that composing speed (or length) and quality were better while students were handwriting as opposed to keyboarding in elementary school (Berninger et al., 2009; Connelly et al., 2007). By contrast, middle school students with HD (Beers et al., 2017) and higher education students with SLD (Berger & Lewandowski, 2013) wrote longer essays while word processing rather than handwriting. These findings suggest that as students grow older, they may benefit more from word processing via keyboarding.…”
Section: Transcription Skills: Handwriting Versus Keyboardingmentioning
confidence: 99%